Insentif Pajak dan Dukungan Fiskall untuk Mendorong Inovasi Kemajuan Teknologi : Sebuah Studi Komparatif - Eddy Mayor Putra Sitepu (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
Human resources and technology are the greatest capital of a nation at this time. Innovation and technology as a driving force of growth re-quires investment in enormous amount. Studies show that tax incentives and fiscal support contribute significantly to the level of investment in research and development. The varying forms of tax incentives and fiscal support results in different impact on the development of technology and innovation. This study aims to conduct a comparative study of the various forms of tax incentives and fiscal support for research and development as well as provide recommendations on the suitable form of tax incentives and fiscal support to be implemented in Indonesia. Methodology used in this research is literature study by using descriptive analysis. There are broadly three forms of tax incentives and fiscal support given in various countries, namely: (i) super deduction; (ii) tax credit; and (iii) direct subsidy. The results of this study indicate that Indonesia needs to take aggressive measures in encouraging innovation and technology to improve global competitiveness. To support these measures, an aggressive tax incentives formulation is also required in the midst of the competition and to keep pace with other countries in the region. Tax incentives given need to be focused on the areas where Indonesia has comparative advantage.